Advances in synthetic microbial ecosystems approach for studying ecological interactions and their influencing factors - Wei Jiang; Sumeng Wang; Fei Gu; Xiaoya Yang; Qingsheng Qi; Quanfeng Liang (Engineering Microbiology)
Investigating ecological interactions within microbial ecosystems is essential for enhancing our comprehension of key ecological issues, such as community stability, keystone species identification, and the manipulation of community structures. However, exploring these interactions proves challenging within complex natural ecosystems. With advances in synthetic biology, the design of synthetic microbial ecosystems has received increasing attention due to their reduced complexity and enhanced controllability. Various ecological relationships, including commensalism, amensalism, mutualism, competition, and predation have been established within synthetic ecosystems. These relationships are often context-dependent and shaped by physical and chemical environmental factors, as well as by interacting populations and surrounding species. This review consolidates current knowledge of synthetic microbial ecosystems and factors influencing their ecological dynamics. A deeper understanding of how these ecosystems function and respond to different variables will advance our understanding of microbial-community interactions.